Purple line Alteration in prediction of labor progress - Morvarid Irani; Masomeh Kordi; Habibollah Esmaeili (Mashhad University of Medical Sciences, 2022)
Introduction: The purple line as a purple point around anus that occurs in the majority of women during labor is one of the non-invasive methods for evaluation of labor progress. This study was performed aimed to determine the diagnostic accuracy of purple line alteration in prediction of labor progress in active phase of labor. Methods: This diagnostic power study was conducted in 2012 on 258 pregnant women with term pregnancy in vertex presentation and beginning of active phase of labor with the appearance of a purple line who were hospitalized in Ommolbanin Hospital. Vaginal examination and purple line observation in the active phase of labor were measured each hour. Sensitivity, specificity, positive and negative predictive value were calculated after determining the cut-off point. Data were collected using the questionnaires: personal-pregnancy information and labor progress form and information about the purple line. Data were analyzed by SPSS statistical software (version 16), ROC curve, sensitivity, specificity, positive and negative predictive value. P<0.05 was considered statistically significant. Results: Increasing the purple line length at each stage of the cervical dilation was associated with the labor progression at that stage. In 3-5 cm cervical dilation, the length of the purple line ≥85 mm was associated with a sensitivity of 93%, specificity 100% and positive predictive value 100%, negative predictive value 33.3% and validity 93.22% with labor progress at the same stage and had the highest diagnostic value Conclusions: Measurement of purple line alteration in the first stage of labor that is, in 3-5 cm cervical dilation, ≥85 mm, 6-8 cm cervical dilation ≥101.5 mm and 9-10 cm cervical dilation ≥110.5 mm was associated with most sensitivity with cervical dilatation and is recommended as a non-invasive method to predict clinical  labor progress in the first stage of delivery.